Elemen-elemen Pembentuk Kota yang Berpengaruh terhadap Citra Kota (Studi Kasus: Kota Lama Semarang) - Wulanningrum, Sintia Dewi (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Kota Lama Semarang is an area where the Dutch colonial where there are buildings constructed since the Dutch era . The old city is often referred to as Little Netherland , with the city -like landscape in Europe and the canals that surround the Old City like making miniature Dutch in Semarang . However, as the development of the times , the image of the Old City of Semarang increasingly undermined by the influence of modernization . This study aims to determine the forming elements which affect the image of the city in the Old Town neighborhood , so it can be used as a reference in enhancing the image in the old town area of Semarang . The research method is qualitative and quantitative . From the analysis , it was found that the elements most influence on the image of the Old Town area is in Zone Lt. Soeprapto as the most prominent landmarks is the Church Blenduk , the district has a specific activity and mass system , where there are activities such as worship , trade and services as well as office . In addition , the most prominent path is on track Lt. Soeprapto which can be seen through the presence of a typical row of buildings on the right side or the left lane.